Factor II Related Antigen and Antithrombin III Levels as Indicators of Liver Failure in Consumption Coagulopathy - Sié, P; Letrenne, E; Caranobe, C; Genestal, M; Cathala, B; Boneu, B (Thrombosis and Haemostasis, 1982)
In order to detect impaired synthesis of blood coagulation factors associated to consumption coagulopathy, a simultaneous evaluation of factor II-related antigen (II rAg) and of antithrombin III (AT III) was carried out in 16 patients affected with severe defibrination. An in vitro preliminary study on plasma and serum demonstrated that the levels of II rAg and of AT III, assessed by the Laurell technique with Behring antisera, were not reduced by the coagulation process. The patients were, a posteriori, classified into two groups according to the absence (group A) or the presence (group B) of factors predisposing to liver failure such as metastasis, cirrhosis, and prolonged shock. II rAg and AT III levels are significantly correlated; they are in the normal range in group A but reduced in group B. Thus II rAg or AT III level determinations are useful markers in the detection of liver failure associated to the consumption phenomenon. These results also suggest that part of the decreased AT III levels reported in severe cases of disseminated intravascular coagulation may be the consequence of an associated liver failure.
Keywords: Antithrombin III; II related antigen; Consumption coagulopathy